Geological study of Pattharkot-Thada area, Arghakhachi district, western Nepal - Devkota, Saugat; Kunwar, Basant; Sigdel, Jitendra; Phullel, Kishan; Poudel, Sujata; Paudel, Roshan; K. C, Ashish; Adhikari, Purushottam; Paudayal, Khum N. (BMC Journal of Scientific Research, 2025)
A comprehensive geological study was carried out in the Siwalik succession of the Pattharkot–Thada region, western Nepal. Structurally, the study area is divided into southern and northern belts, demarcated by the Central Churia Thrust (CCT). Stratigraphically, the succession is classified into three distinct litho-units, such as the mudstone-dominated Lower, sandstone dominated Middle, and conglomerate-dominated Upper Siwalik, based on their lithological variations. Magnetostratigraphic evidence from the nearby Siwalik regions suggests the deposits in this area to be a transition from Lower to Middle Siwalik that occurred before or around 8.5 million years ago, while the shift from the Middle to Upper Siwalik was established approximately 2.5 million years ago. Additionally, the deposition the Siwalik succession was laid down by localized fluvial systems, representing an interfluve zone within a broader fluvial network.